The story of Jesus in history and faith - McDonald, Lee Martin, 1942- (Grand Rapids, Michigan : Baker Academic, a Division of Baker Publishing Group, 2013)
"Many books are available on the historical Jesus, but few address issues that are critically central to Christian faith--namely, Jesus as resurrected Lord, Christ, and Son of God. This comprehensive introduction to the study of the historical Jesus takes both scholarship and Christian faith seriously. Leading New Testament scholar Lee Martin McDonald brings together two critically important dimensions of the story of Jesus: what we can know about him in his historical context and what we can responsibly claim about his significance for faith today. McDonald examines the most important aspects of the story of Jesus from his birth to his resurrection and introduces key issues and approaches in the study of the historical Jesus. He also considers faith issues, taking account of theological perspectives that secular historiography cannot address. The book incorporates excerpts from primary sources and includes a map and tables" -- Publisher description.
Pt. 1 History and the historical Jesus. History, historical inquiry, and the historical Jesus -- Pt. 2 Sources for studying the historical Jesus. The Gospels: their relationships and reliability -- Other sources for studying the historical Jesus -- Pt. 3 The story of Jesus in history (events and teachings). The story of Jesus in history: from His birth to His scriptures -- The story of Jesus in history: from the transfiguration to His burial -- Easter: the story of Jesus within history and faith -- Conclusion: Jesus in history and faith.
Includes bibliographical references (pages 347-365) and indexes.
Keywords: Jesus Christ -- Historicity